Serum tissue inhibitor of metalloproteinase‐1 and risk of cognitive impairment after acute ischaemic stroke. Issue 13 (20th May 2020) - Ge, Jinzhuo; Li, Ruyi; Yuan, Pengcheng; Che, Bizhong; Bu, Xiaoqing; Shao, Hancheng; Xu, Tan; Ju, Zhong; Zhang, Jintao; Zhang, Yonghong; Zhong, Chongke
Abstract: The expression of tissue inhibitor metalloproteinase‐1 (TIMP‐1) significantly increased after acute cerebral ischaemia and involved in neurodegeneration. The purpose was to prospectively investigate the relationship between serum TIMP‐1 with post‐stroke cognitive impairment. Our participants were from an ancillary study of China Antihypertensive Trial in Acute Ischemic Stroke. 598 ischaemic stroke patients from seven participating hospitals were included. Cognitive impairment was evaluated using Mini‐Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) at 3 months. 316 (52.84%) or 384 (64.21%) participants had cognitive impairment according to MMSE or MoCA, respectively. Compared with the first quartile of TIMP‐1, the multivariate‐adjusted odds ratios (95% confidence intervals) for the highest quartile were 1.80 (1.09‐2.97) for cognitive impairment defined by MMSE and 2.55 (1.49‐4.35) by MoCA. Multiple‐adjusted spline regression models showed linear associations between TIMP‐1 concentrations and cognitive impairment ( P value for linearity < 0.01). The addition of TIMP‐1 to models including conventional factors improved reclassification for cognitive impairment, as shown by net reclassification index or integrated discrimination improvement ( P < 0.05). Participants with both higher TIMP‐1 and matrix metalloproteinase‐9 levels simultaneously had highest risk of cognitive impairment. Higher serum TIMP‐1 levels were associated with increased risk of cognitive impairment after acute ischaemic stroke, independently of established risk factors.